Respiratory Trajectory after Invasive Interventions for Patent Ductus Arteriosus of Preterm Infants - Yu-Jen Wei; Yen-Ju Chen; Yung-Chieh Lin; Chung-Dann Kan; Min-Ling Hsieh; Yuh-Jyh Lin; Jing-Ming Wu; Jieh-Neng Wang (Children, 2021)
Invasive interventions have been conducted in preterm infants with significant patent ductus arteriosus (PDA) when medical treatment has failed, and methods of invasive intervention have been reported. Surgical ligation via lateral thoracotomy has been a well-established procedure for decades. Recently, transcatheter occlusion has been safely and feasibly applied to the premature population. However, little research has been conducted on the benefits of transcatheter occlusion in very-low-birth-weight (VLBW) infants compared to surgical ligation. This study compared transcatheter and surgical techniques in VLBW infants in terms of short-term respiratory outcomes. The medical records of 401 VLBW infants admitted to a tertiary hospital between September 2014 and January 2019 were retrospectively reviewed. Patients who were diagnosed with a congenital anomaly, a chromosomal anomaly, or congenital heart disease, except for an inter-atrial shunt, were excluded. The perinatal conditions, neonatal morbidities, periprocedural vital signs, and respiratory support trajectories were compared between the transcatheter-treated and surgically ligated group. A total of 31 eligible VLBW infants received invasive intervention: 14 were treated with transcatheter occlusion (Group A), and 17 infants were treated with surgical ligation (Group B). Respiratory outcomes were not statistically significant between the two groups, despite Group A showing a trend toward early improvement in post-intervention respiratory trajectory. In this small case study, a different trend in post-intervention respiratory trajectories was observed. Future research with larger case numbers should be conducted to address our preliminary observations in more detail.